Answers to your biggest questions about teaching elementary math - SanGiovanni, John; Knighten, Latrenda; Rivera, Georgina; Katt, Susie (Susie K.) (Corwin mathematics, 2022)
"Designed for just-in-time learning and support, this quick-reference guide gives you brief and digestible answers to your most pressing questions about teaching elementary math. Written by four seasoned math educators, it offers the guidance and advice these educators wish they had years ago, lessons they've learned over decades of practice, research, coaching, and through working with math teachers-especially new teachers-every day. These questions are organized into five areas of effort that will help you most thrive in your elementary math classroom"--